Contesting Unfreedom: To be Queer and Christian in the Philippines - Cornelio, Jayeel (The review of faith & international affairs, 2022)
Queer Filipinos continue to experience different modes of discrimination, abuse, and coercion, mainly because of conservative religious worldviews. They encounter these experiences in their households, schools, workplaces, and churches, which we refer to as spaces of unfreedom. How do queer Filipinos navigate these spaces of unfreedom? We answer this based on interviews with queer young adult men who grew up Christian in various denominations. We argue that they are in an ongoing process of contesting unfreedom through moral, theological, and aspirational reasoning. We conclude by making a case for robust religious freedom for LGBTQ+ persons—one which goes beyond the legal discourse and recognizes their spaces of unfreedom.